2001
DOI: 10.1063/1.1376659
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of Mn-implanted GaN

Abstract: High doses (10 15-5ϫ10 16 cm Ϫ2) of Mn ϩ ions were implanted into p-GaN at ϳ350°C and annealed at 700-1000°C. At the high end of this dose range, platelet structures of Ga x Mn 1Ϫx N were formed. The presence of these regions correlated with ferromagnetic behavior in the samples up to ϳ250 K. At low doses, the implanted led to a buried band of defects at the end of the ion range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
169
1
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 280 publications
(180 citation statements)
references
References 26 publications
5
169
1
2
Order By: Relevance
“…Since the Curie temperature is predicted to be a strong function of bandgap, magnetic ion concentration and carrier concentration in the semiconductor, it has been proposed that materials with gaps much larger than GaAs and InAs should be investigated [9]. There has been some success in initial experiments on (Ga,Mn)N, prepared either by bulk growth processes [10,11] or direct implantation of Mn into GaN [12,13]. The bulk crystals exhibit paramagnetic behavior, while the implanted GaN shows ferromagnetic contributions to the magnetism below Â/250 K.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Curie temperature is predicted to be a strong function of bandgap, magnetic ion concentration and carrier concentration in the semiconductor, it has been proposed that materials with gaps much larger than GaAs and InAs should be investigated [9]. There has been some success in initial experiments on (Ga,Mn)N, prepared either by bulk growth processes [10,11] or direct implantation of Mn into GaN [12,13]. The bulk crystals exhibit paramagnetic behavior, while the implanted GaN shows ferromagnetic contributions to the magnetism below Â/250 K.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the ferromagnetic behavior of Mn-implanted GaN could be due to the formation of a Mn 3 Ga phase. 4 Thus, it is suggested that the Ga-Mn bond may originate from a binary phase of Ga-Mn. No observation of Ga-Mn phases could be attributed to the nanoscale size and the random orientation.…”
mentioning
confidence: 99%
“…5 The ferromagnetic property was also reported in Mn-implanted GaN with subsequent annealing. 4 However, some phases could be formed in the films due to the low solubility of magnetic ions in GaN, such as ferromagnetic Ga-Mn and ferrimagnetic Mn-N compounds. These precipitates could give a major contribution to the total magnetic moment of the samples.…”
mentioning
confidence: 99%
See 2 more Smart Citations